2004
DOI: 10.1128/aac.48.9.3559-3562.2004
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Macrolide-Resistant Streptococcus pyogenes Strains in French Children

Abstract: We studied the antimicrobial susceptibility of 322 Streptococcus pyogenes throat isolates from French children and their serotype and genomic diversity. A total of 22.4% were erythromycin resistant, and 69.4, 4.2, and 26.4% of these isolates harbored ermB, ermA, and mefA, respectively. Increasing resistance in France is mainly associated with a few emm type 28 clones.Streptococcus pyogenes pharyngitis is one of the most common bacterial upper respiratory tract infections in children. Group A streptococci (GAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
3
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 18 publications
8
55
3
8
Order By: Relevance
“…This is the first study on genotypic analysis of erythromycin resistance among the GAS strains isolated from skin and soft tissue infections showing predominance of ermB gene. The similar ermB predominance was also reported earlier from Belgium, France and Italy [20][21][22].…”
Section: Discussionsupporting
confidence: 72%
“…This is the first study on genotypic analysis of erythromycin resistance among the GAS strains isolated from skin and soft tissue infections showing predominance of ermB gene. The similar ermB predominance was also reported earlier from Belgium, France and Italy [20][21][22].…”
Section: Discussionsupporting
confidence: 72%
“…The strains with emm28 showed a high ERY resistance rate (58.3%), suggesting that strains with this emm genotype are highly resistant. All erm(B)-positive ERY-resistant GAS isolates had an emm28 genotype, which accounts for 50% and 70% of erm(B)-positive ERY-resistant GAS isolates in North America [21] and France [6], respectively. In our previous study (2002), the ERY resistance rate of emm12 strains was 63%, and most of them had the cMLSB phenotype, whereas emm18 and emm75 strains had the M phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Finland, Spain, and Italy have shown a strong correlation between macrolide usage and resistance of GAS (501)(502)(503). A rapid increase in the percentage of macrolide-resistant strains may also be due to the clonal expansion of a single resistant strain (442,498,504). Many countries have instituted a more restrictive use of macrolides in response to alarming reports of high rates of macrolide resistance among GAS strains.…”
Section: Resistance To Macrolidesmentioning
confidence: 99%